Hybrid threats in the national security context of Nepal - Angbo, Padam Kumar (Unity Journal, 2020)
Of late, hybrid warfare has emerged as a widely contested but practically tested war strategy anticipated in the future. This paper revolves around strategies to deter, mitigate and counter hybrid threats to national security in the context of Nepal. Prevailing geopolitical and geostrategic environments exhibit that different actors, including state and non-state hybrid strategies pose a clear challenge to Nepal's national security interests. Hence, there is a need for a national security strategy to counter hybrid threats which demands fresh thinking, expanding the traditional enemy-centric threat assessment and response. But the general understanding of hybrid warfare is underdeveloped because hybrid means are ambiguous and complex, such as unorthodox, unpredictable and constantly changing. Ultimately, developing and implementing effective national security policy, ensuring political stability, zero tolerance policy on corruption, good governance, economic and resources development, trusted law enforcement, effective stakeholders including security and intelligence system, building resilience are the best ways to prevent a hybrid war before it erupts. This article argues that Nepali Army, as a key responder, too needs to have an updated military doctrine and strategy on its role in countering it.